AN ANALYSIS OF STUDENTS’ WRITING SKILLS IN PARAPHRASING: A CASE STUDY OF THE 5TH-SEMESTER DIPLOMA STUDENTS OF ENGLISH LANGUAGE AND CULTURE DEPARTMENT OF DARMA PERSADA UNIVERSITY - Yoga Pratama; Anjar Prawesti; Fridolini (English Education Department, 2022)
It is significant for students to have competence in writing research papers that requires writing skills. Using formal language and avoiding plagiarism are mandatory for academic paper writers. Paraphrasing is one of the writing skills, which can be interpreted as rewriting a source text using the writers’ own words by changing it syntactically or semantically while maintaining the main idea. Other than investigating the barriers to paraphrasing and how to overcome them, this research aims to analyze the paraphrasing strategy generally applied by the 5th-semester Diploma students of the English Language and Culture Department of Darma Persada University. By approaching mixed-research methods, this study uses a questionnaire and a writing task as the instruments. Likert Scale is used as a data collection technique in the quantitative research method, which is further processed using SPSS. Meanwhile, the qualitative research method approaches Keck’s Taxonomy of Paraphrasing Types and the paraphrasing strategies by Jackie Pieterick. The analysis results find that the majority of the students have difficulties in paraphrasing. A lack of vocabulary and using their own words become their barriers to paraphrasing. In that case, comprehensive learning about paraphrasing skills and strategies taught by lecturers or educators are expected to overcome the obstacles. Furthermore, using synonyms becomes the paraphrasing strategy generally applied by the students. The paraphrased version of the writing task also indicates that the students try not to copy similar words or sentences from the source and therefore the most of the paraphrasing results are included in the Minimal Revision.